2017
DOI: 10.18203/2319-2003.ijbcp20173148
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance in cancer chemotherapy in regional cancer center of Eastern India: prospective observational study

Abstract: Background: Globally cancer is the leading cause of morbidity and mortality with annual death rate of 12%. According Indian Council of Medical Research, more than 1300 Indians die every day due to cancer. Chemotherapy is one of the multimodal approaches for treatment of cancer and regimens are much complex and cancer patients are more susceptible to adverse drug reaction with little tolerance due to diminished immunity. The present study was done to evaluate the prevalence of various adverse drug reactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This is in accordance with study by Surendiran et al 23 The mechanism of chemotherapy induced nausea and vomiting is through activation of chemoreceptor trigger zone. 24,25 In relation to the organ system, our results are consistent with the previous studies, 16 where the reactions affecting gastrointestinal tract were found to be among the most frequently affected ADRs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in accordance with study by Surendiran et al 23 The mechanism of chemotherapy induced nausea and vomiting is through activation of chemoreceptor trigger zone. 24,25 In relation to the organ system, our results are consistent with the previous studies, 16 where the reactions affecting gastrointestinal tract were found to be among the most frequently affected ADRs.…”
Section: Discussionsupporting
confidence: 90%
“…It is consistent with the study done by Rademaker M et al 14 The reason for this increased risk includes gender related differences in pharmacokinetics, immunological and hormonal factors. 15,16 Women generally have lower body mass, reduced hepatic clearance and metabolize drugs at different rates compared to men. 17 This variation can also be due to difference in medications and treatment guidelines followed in different setups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of cancer treatment options, patients are vulnerable to adverse drug reactions for a variety of reasons, including poor drug adherence and clinical conditions. 11 As a result, poor chemotherapy adherence leads to drug resistance, recurrence, and poor quality of life in patients, negatively impacting the nation's health costs and ultimately resulting in mortality. 12 Chemotherapy adherence is strongly related to patientrelated factors, therapy-related factors, condition-related factors, healthcare system factors, and socioeconomic factors.…”
Section: Introductionmentioning
confidence: 99%
“…14,17 Although cancer treatment options exist, patients become vulnerable to ADR due to various reasons, including poor adherence to drugs and clinical conditions. 18 For a number of formerly fatal malignancies, such as lymphomas and leukemias, chemotherapy treatment is curative. Although anti-cancer drugs are well studied and highly beneficial for better treatment outcomes, when compared to other classes of medications, they are associated with various forms of adverse drug reactions (ADRs).…”
Section: Introductionmentioning
confidence: 99%